Effect of Thiophenone Compound on Motility and Caseinase Production of Aeromonas hydrophila - Sinaga, Ayu Ashari Margareth; Julyantotro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Advances in Tropical Biodiversity and Environmental Sciences; Vol 5 No 2 (2021): ATBES, 2021)
Motility and caseinase production are part of bacterial virulence factors which are regulated by a bacterial intercellular communication system, often called quorum sensing (QS). This study aims to determine the effect of the QS inhibitor compound thiophenone in reducing those virulence factors. This research was conducted at the Laboratory of Fisheries Science, Faculty of Marine Science and Fisheries, Udayana University, from December 2019 to March 2020. This study tested 3 different treatments with 3 repetitions for each treatment. Treatment A as control (without the addition of thiophenone), treatment B (addition of 5 ?M thiophenone), and C treatment (addition of 10 ?M thiophenone). The results showed that thiophenone compounds can inhibit the QS system of Aeromonas hydrophila . It can be seen from the significantly reduced (P<0.05) motility and caseinase enzyme activity of A. hydrophila compared to without addition of thiophenone compounds. The average diameter of the caseinase enzyme production produced in treatment A at 22 hours was 21.40±0.36 mm, in treatment B was 19.70±0.2 mm and in treatment, C was 17.87±0.05 mm. Whereas in motility, the resulting average diameter in treatment A at 22 hours was 6.57±0.61 mm, in treatment B was 5.67±0.35 mm and in treatment, C was 5.10±0.6 mm. These results indicate that the QS thiophenone inhibitor compound can reduce virulence factors, namely motility and caseinase production from pathogenic bacteria A. hydrophila. Treatment C can decrease virulence factors compared to treatment A and B.